REVIEW OF FIQH SIYASAH ON IMPLEMENTATION MEDAN CITY REGULATION NO. 1 OF 2017 CONCERNING PARKING TAX (CASE STUDY OF PT. MARAPYOSIN KENCANA BUANA (BUANA PARKING)) AT RS. COLUMBIA ASIA MEDAN CITY - Azmi Azmi Batubara; Fitri Chairani Panjaitan; Firanti Andari Nasution; Bob Feinberg (PT. Radja Intercontinental Publishing, 2023)
This article aims to find out the comparison of parking rates applied and serve as a guideline in implementing the provisions regulated in the Medan City Regional Regulations (Medan City Regulation No. 1 of 2017 concerning parking tax) with the parking regulations stipulated by the Columbia Asia Hospital, Medan City. a review seen from the aspect of Fiqh Siyasah. This writing is motivated by various forms of problems which are used as complaints experienced by several consumers when using parking services which are considered less effective and the services provided are not commensurate with the rates set. The research method used is the Empirical Juridical method with a descriptive analysis approach. The results of this research indicate that the implementation of Medan City Regional Regulation no. 1 of 2017 has been running well and optimally, however, it has not been fully implemented by entrepreneurs from private companies who collaborate with Columbia Asia Hospital, Medan City, this is due to the profit factor obtained from collecting parking fees, as well as the absence of proper supervision. carried out by the Medan City Government as the implementer of public policy towards private parking entrepreneurs. According to the siyasah fiqh analysis, the implementation of Regional Regulation Number 1 of 2017 on parking rate policies in Medan City has not been fully implemented optimally in accordance with Islamic principles and siyasah fiqh rules. This is due to the profit factor obtained from quoting parking rates, as well as the absence of supervision carried out by the Medan City Government as the implementer of public policy towards private parking entrepreneurs. According to the siyasah fiqh analysis, the implementation of Regional Regulation Number 1 of 2017 on parking rate policies in Medan City has not been fully implemented optimally in accordance with Islamic principles and siyasah fiqh rules. This is due to the profit factor obtained from quoting parking rates, as well as the absence of supervision carried out by the Medan City Government as the implementer of public policy towards private parking entrepreneurs. According to the siyasah fiqh analysis, the implementation of Regional Regulation Number 1 of 2017 on parking rate policies in Medan City has not been fully implemented optimally in accordance with Islamic principles and siyasah fiqh rules.